Multimodal pattern recognition of social signals in human-computer-interaction : 4th IAPR TC 9 Workshop, MPRSS 2016, Cancun, Mexico, December 4, 2016, Revised selected papers /: 4th IAPR TC 9 Workshop, MPRSS 2016, Cancun, Mexico, December 4, 2016, Revised selected papers. (2017) - Unknown
No abstract available